Effect of Melatonin Supplementation on Antioxidant Status and DNA Damage in High Intensity Trained Athletes - Ortiz-Franco, Manuel; Planells, Elena; Quintero, Bartholomé; Acuña-Castroviejo, Dario; Rusanova, Iryna; Escames, Germaine; Molina-López, Jorge (International Journal of Sports Medicine, 2017)
The aim of the study was to evaluate the effect of melatonin supplementation on antioxidant capacity and DNA damage in high intensity interval training (HIIT) athletes. A 2-week randomised, double-blinded, placebo-controlled trial with two groups was conducted. Placebo (PG) and melatonin (MG) (20 mg/d) athletes were monitored over a two-week period of HIIT and strength training. The total antioxidant capacity (TAC) and the glutathione peroxidase (GPx) and superoxide dismutase (SOD) activities were analysed in blood samples. DNA damage was measured in isolated lymphocytes by comet assay prior to and immediately after exercise. The supplementation increased plasma melatonin levels in the melatonin-treated group (p<0.05) after two weeks of intervention. Analysis of antioxidant status indicated higher (p<0.05) TAC and GPx in MG than PG post-intervention. No differences were found in SOD enzyme activity. DNA damage was diminished in MG (p<0.05) compared to PG in post-training conditions. Antioxidant status was associated with DNA damage (r=-0.679; p=0.047) in the melatonin-treated athletes. The present study suggest that melatonin supplementation improves antioxidant status and may prove to have beneficial effects preventing DNA damage induced by high intensity training.
Keywords: Melatonin; antioxidant status; DNA damage; comet assay; high-intensity interval training